Manipulating culture conditions and feed quality to increase the survival of larval marble goby oxyeleotris marmorata - Loo, P.L.; Chong, V.C.; Ibrahim, S.; Sabaratnam, V. (TAYLOR & FRANCIS INC, 530 WALNUT STREET, STE 850, PHILADELPHIA, PA 19106 USA, 2015)
Fish stocking density, feed quality, and tank color were evaluated for their effects on survival of larval Marble Goby Oxyeleotris marmorata reared at 5-g/L salinity for 30 d. Feed quality was examined in terms of proximate composition and fatty acid profile. Fish larvae were given rotifers and brine shrimp Artemia spp. nauplii (R-A) that were fed condensed cells of the phototrophic bacterium Rhodovulum sulfidophilum (bPB) cultured in palm oil mill effluent (POME); under this feeding regime, fish stocked at a density of 15 larvae/L had significantly higher survival (42.0) than those stocked at 20 larvae/L (33.5) or 30 larvae/L (9.9). At the best stocking density of 15 larvae/L, fish survival and growth were further improved when the larvae received either R-A that were fed the whole culture broth of unsettled bacteria (cPB; survival = 60.9) or R-A that were fed POME (survival = 58.6). Under similar rearing conditions, larvae reared in gray-colored tanks showed still further significant improvement in survival (79.0) relative to larvae that were reared in black tanks (32.5) or transparent tanks (0.7). Thus, optimal culture conditions for larval survival (71.4-81.9) included rearing in gray culture tanks, stocking at 15 larvae/L, and a diet of R-A that were fed cPB or bPB. Under those optimal conditions, survival during the critical larval period (first 10 d posthatch; 91.4-95.7) was significantly improved. An approximate 2: 2: 1 dietary ratio of docosahexaenoic acid : eicosapentaenoic acid : arachidonic acid as compared to a fish tissue ratio of 7: 2: 1 is recommended to improve the survival and production of Marble Goby larvae.